2022
DOI: 10.1155/2022/8191253
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Flavonoids in Allergies: A Systematic Review of Randomized Controlled Trials

Abstract: Objective. To assess the clinical efficacy of flavonoid supplements on allergic diseases. Design. Systematic review. Data Sources. MEDLINE/PubMed, Scopus, Web of Science, and Embase databases were searched from inception to September 2021. Eligibility Criteria for Selecting Studies. Eligible study designs were randomized controlled trials that investigated the effect of flavonoids applied to allergic diseases. Results. This review included 15 randomized controlled trials, including allergic rhinitis/cedar poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Propolis showed inhibitory effects on myeloperoxidase activity, ornithine decarboxylase, tyrosine-protein-kinase, NADPH-oxidase, and hyaluronidase from guinea pig mast cells. This anti-inflammatory activity can be explained by the presence of active flavonoids and cinnamic acid derivatives such as acacetin, quercetin, naringenin and CAPE and CA [ 69 , 70 , 71 , 105 , 106 , 107 , 108 , 109 , 110 ]. Conversely, Ahangari et al [ 57 ] demonstrated that the ethanolic extract of propolis (3, 10, 30, and 100 µg/mL) did not show significant effects on the histamine release induced by ionophore A23187 and ovalbumin.…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
See 3 more Smart Citations
“…Propolis showed inhibitory effects on myeloperoxidase activity, ornithine decarboxylase, tyrosine-protein-kinase, NADPH-oxidase, and hyaluronidase from guinea pig mast cells. This anti-inflammatory activity can be explained by the presence of active flavonoids and cinnamic acid derivatives such as acacetin, quercetin, naringenin and CAPE and CA [ 69 , 70 , 71 , 105 , 106 , 107 , 108 , 109 , 110 ]. Conversely, Ahangari et al [ 57 ] demonstrated that the ethanolic extract of propolis (3, 10, 30, and 100 µg/mL) did not show significant effects on the histamine release induced by ionophore A23187 and ovalbumin.…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
“…These results indicate that CAPE is effective in the systemic anaphylaxis model, indicating that CAPE-mediated anti-allergic effects may be the result of its protective effects against IgE-mediated allergy [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 100 ]. CAPE effectively reduced the infiltration of monocytes and neutrophils and inhibited the activation of TLR by interrupting interaction of the ligand (LPS) with the receptor complex (TLR4/MD2) [ 108 , 109 ]. CAPE successfully affects several cellular oxidative processes: (1) inhibits myeloperoxidase activity (MPO) by PMN infiltration; (2) reduces respiratory burst of human PMN; and (3) forms oxide-base in epidermal DNA isolated in mice treated in vivo [ 109 ].…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
See 2 more Smart Citations
“…129 Future clinical research studies may want to consider comparing differences in the efficacy of bitter among patients with varying TAS2R SNPs, as inconsistencies and heterogeneity in therapeutic efficacy of flavonoids for asthma have been noted across several studies. 130 Similarly, MP-AzeFlu (Dymista ® ; spray of azelastine/fluticasone propionate) is a drug used for allergic rhinitis and its dilatory effects on pre-contracted airways are thought to be enhanced by T2R activation rather than through blocking histamine receptors. 131 Investigations can be conducted on the specific receptor isoforms that MP-AzeFlu activates and whether its efficacy is affected by T2R polymorphisms of the host.…”
mentioning
confidence: 99%